The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1161/circimaging.112.000153
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Left Atrial Appendage Thrombus by Cardiac Computed Tomography in Patients With Atrial Fibrillation

Abstract: Background-Transesophageal echocardiogram (TEE) is considered the gold standard modality in detecting left atrial/ LA appendage (LA/LAA) thrombi. However, this is a semi-invasive procedure with rare but potential life-threatening complications. Cardiac computed tomography has been proposed as an alternative method. The purpose of this metaanalysis was to evaluate the diagnostic accuracy of cardiac computed tomography assessing LA/LAA thrombi in comparison with TEE. Methods and Results-A systematic review of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
232
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(241 citation statements)
references
References 52 publications
(28 reference statements)
2
232
1
6
Order By: Relevance
“…A recent meta-analysis demonstrated that the overall high accuracy of cardiac CT, compared with TEE, can be used to detect LA or LAA thrombus in patients with AF. The investigators included 19 studies with a total of 2955 patients and found the weighted mean sensitivity and specificity to be 96% (95% CI: 92-100%) and 92% (95% CI: 91-93%), whereas the PPV and NPV were 41% (95% CI: 37-44%) and 99% (95% CI: 99-100%), respectively [52]. This is because a pseudo-filling defect, such as flow stasis, can also cause an apparent filling defect on CT images, thereby mimicking a thrombus.…”
Section: Cardiac Computed Tomographymentioning
confidence: 99%
“…A recent meta-analysis demonstrated that the overall high accuracy of cardiac CT, compared with TEE, can be used to detect LA or LAA thrombus in patients with AF. The investigators included 19 studies with a total of 2955 patients and found the weighted mean sensitivity and specificity to be 96% (95% CI: 92-100%) and 92% (95% CI: 91-93%), whereas the PPV and NPV were 41% (95% CI: 37-44%) and 99% (95% CI: 99-100%), respectively [52]. This is because a pseudo-filling defect, such as flow stasis, can also cause an apparent filling defect on CT images, thereby mimicking a thrombus.…”
Section: Cardiac Computed Tomographymentioning
confidence: 99%
“…Studies with mutlidetector CT have reported good sensitivity and specificity for CCTA for LAA thrombus detection [46,47]. Recent meta-analysis demonstrated that CT shows a good diagnostic accuracy in detecting LA/ LAA thrombus with high sensitivity and specificity [48,49]. This technique has a high negative predictive value for excluding LAA thrombus.…”
Section: Thrombusmentioning
confidence: 99%
“…Adaptation to CCTA protocols may improve LAA thrombus detection: delayed imaging (2-phase scan with delayed image acquisition at least 30 seconds after contrast bolus), dual-enhanced scan (single scan after 2-bolus contrast), dual-energy source and prone position [50,51]. When delayed imaging was performed, the diagnostic accuracy significantly improved across different studies [49]. Hence, CCTA, particularly when delayed imaging is performed, may be a reliable alternative for the detection of LA or LAA thrombi.…”
Section: Thrombusmentioning
confidence: 99%
“…Si bien el ecocardiograma transesofágico es considerado como la regla de oro para la evaluación de la orejuela izquierda y la detección de trombos, se trata de un procedimiento semiinvasivo, en ocasiones mal tolerado y con potenciales complicaciones. Estudios recientes con TC multicorte han demostrado que se trata de una técnica útil, rápida y precisa en la detección de trombos, convirtiéndose en una alternativa válida al ecocardiograma transesofágico 17 . Al mismo tiempo, permite una valoración rápida y completa de la anatomía y dimensiones de la orejuela izquierda previa al cierre con dispositivos, así como un control de su posicionamiento tras el implante 18 (fig.…”
Section: Figuraunclassified